2017
DOI: 10.15405/epsbs.2017.09.4
|View full text |Cite
|
Sign up to set email alerts
|

Hypericumperforatum L. Showed Antinociceptive Effects Through Opioidergic And Serotonergic Systems

Abstract: There are some reports concerning the antidepressant effects of Hypericumperforatum L.(Hp), but there are few studies indicating its antinociceptive effects of Hp. For assessment of its site of antinociceptive action and related systems, Hp was filtered and administered both intrathecally (i.t.) and intracerebroventriculary(i.c.v.). For evaluation of probable role of serotonergic and opioidergic systems, Methysergide (non-selective antagonists of serotonergic systems) andnaloxone hydrochloride (antagonist of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Studies have reported the antinociceptive effects of Allium species such as A. ampeloprasum (Abbas, 2019 ) and A . jesdianum (Khaksarian et al., 2008 ). In studies using the hotplate test, it has been shown that different Allium species generally delay the response time to pain compared to the control group in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the antinociceptive effects of Allium species such as A. ampeloprasum (Abbas, 2019 ) and A . jesdianum (Khaksarian et al., 2008 ). In studies using the hotplate test, it has been shown that different Allium species generally delay the response time to pain compared to the control group in animals.…”
Section: Discussionmentioning
confidence: 99%